2015
DOI: 10.1055/s-0035-1563382
|View full text |Cite
|
Sign up to set email alerts
|

Mastoid Obliteration with Autologous Bone in Mastoidectomy Canal Wall Down Surgery: a Literature Overview

Abstract: Introduction The objectives of mastoidectomy in cholesteatoma are a disease-free and dry ear, the prevention of recurrent disease, and the maintenance of hearing or the possibility to reconstruct an affected hearing mechanism. Canal wall down mastoidectomy has been traditionally used to achieve those goals with greater or lesser degrees of success. However, canal wall down is an aggressive approach, as it involves creating an open cavity and changing the anatomy and physiology of the middle ear and mastoid. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
(37 reference statements)
3
25
0
1
Order By: Relevance
“…Most studies so far have reported outcomes of CWD surgery with reconstruction of the posterior canal wall and obliteration of the mastoid using varying techniques . Furthermore, although MRI‐DWI has proven to be the most reliable noninvasive technique to detect recurrent or residual cholesteatoma, almost all studies used otoscopy and/or computed tomography (CT) as follow‐up, sometimes combined with a second look at the nonobliterated middle ear only .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies so far have reported outcomes of CWD surgery with reconstruction of the posterior canal wall and obliteration of the mastoid using varying techniques . Furthermore, although MRI‐DWI has proven to be the most reliable noninvasive technique to detect recurrent or residual cholesteatoma, almost all studies used otoscopy and/or computed tomography (CT) as follow‐up, sometimes combined with a second look at the nonobliterated middle ear only .…”
Section: Discussionmentioning
confidence: 99%
“…Another argument may be that residual skin is not able to develop into cholesteatoma in a bony obliterated space, which is called the Hinohira effect . Regardless of the causative mechanism, obliteration seems to improve the outcome of cholesteatoma surgery in a variety of studies using different materials for obliteration, ranging from autologous material (e.g., cartilage, bone, musculoperiosteal flaps) to biocompatible alloplastic materials (e.g., hydroxyapatite, bioactive glass) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mastoid obliteration is used to reduce the recurrence and the residual rate in primary cholesteatoma surgery using both canal-wall-up 4,5 and canal-wall-down procedures. 14,19,20 Moreover, obliteration of an unstable mastoid cavity leads to significantly better results for discharge, 1,21,22 hearing rehabilitation 23 and imbalance 3 than a revision canal-wall-down procedure. 24 Since 1911, 25 many materials, either autologous or biocompatible, have been used for obliteration.…”
Section: Discussionmentioning
confidence: 99%
“…A külső hallójárat porcos és csontos szakaszának határán a bőrt teljesen átvágjuk (anterior irányba is) (2/B ábra). A bőrt gondosan leválasztjuk a tragus porcáról, illetve körkörösen felpreparáljuk, majd a hallójáraton keresztül kifordítjuk [10][11][12]. A kifordított bőrcső anterior és posterior széleit 3.0-ás Vicryl fonallal összevarrjuk (2/C ábra).…”
Section: Műtéti Technikaunclassified